2014
DOI: 10.1021/la501962n
|View full text |Cite
|
Sign up to set email alerts
|

Oleic Acid Phase Behavior from Molecular Dynamics Simulations

Abstract: Fatty acid aggregation is important for a number of diverse applications: from origins of life research to industrial applications to health and disease. Experiments have characterized the phase behavior of oleic acid mixtures, but the molecular details are complex and hard to probe with many experiments. Coarse-grained molecular dynamics computer simulations and free energy calculations are used to model oleic acid aggregation. From random dispersions, we observe the aggregation of oleic acid monomers into mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 46 publications
5
49
1
Order By: Relevance
“…During the prandial period, this pH microclimate might also favor the ionization of LCFA released by lingual lipase from dietary TG. Although the pK a value of LCFA is always discussed (87,90), OLA monomers in water appear to be essentially ionized at neutral pH (87). This physicochemical characteristic might maintain LCFA in the extracellular environment of the TBC because the plasma membrane is poorly permeable to ionized LCFA, in contrast to their protonated forms (89).…”
Section: Influence Of the Salivary Environmentmentioning
confidence: 99%
“…During the prandial period, this pH microclimate might also favor the ionization of LCFA released by lingual lipase from dietary TG. Although the pK a value of LCFA is always discussed (87,90), OLA monomers in water appear to be essentially ionized at neutral pH (87). This physicochemical characteristic might maintain LCFA in the extracellular environment of the TBC because the plasma membrane is poorly permeable to ionized LCFA, in contrast to their protonated forms (89).…”
Section: Influence Of the Salivary Environmentmentioning
confidence: 99%
“…Previous studies have shown that the apparent pKa of oleic acid in different surfactant and lipid mixtures ranges from 6.0 to 9.5. For example, the pKa of pure oleic acid vesicles is 8.0- 9.5 [27,42,43]. While when mixed with monoolein, the pKa was 6.0-7.0 [24].…”
Section: Dissociation Of Oleic Acid In Mixed 7:3 Dppc-oleic Acid Membmentioning
confidence: 99%
“…We did this to obtain OA aggregates that were as similar as possible to the aggregates of the liprotide core, which consist of deprotonated OA . Increasing protonation first causes micelle elongation and eventually bilayer structure formation as determined previously with the MARTINI force field, and this is not likely to be relevant for the liprotides. To determine the amount of OA molecules per micelle to use in this study we performed a CG MD simulation on a solution of 500 OA molecules in water (0.06 wt %) over the course of 1 μs.…”
Section: Resultsmentioning
confidence: 60%